If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y(2y + -3) = (2y + -3) Reorder the terms: 5y(-3 + 2y) = (2y + -3) (-3 * 5y + 2y * 5y) = (2y + -3) (-15y + 10y2) = (2y + -3) Reorder the terms: -15y + 10y2 = (-3 + 2y) Remove parenthesis around (-3 + 2y) -15y + 10y2 = -3 + 2y Solving -15y + 10y2 = -3 + 2y Solving for variable 'y'. Reorder the terms: 3 + -15y + -2y + 10y2 = -3 + 2y + 3 + -2y Combine like terms: -15y + -2y = -17y 3 + -17y + 10y2 = -3 + 2y + 3 + -2y Reorder the terms: 3 + -17y + 10y2 = -3 + 3 + 2y + -2y Combine like terms: -3 + 3 = 0 3 + -17y + 10y2 = 0 + 2y + -2y 3 + -17y + 10y2 = 2y + -2y Combine like terms: 2y + -2y = 0 3 + -17y + 10y2 = 0 Factor a trinomial. (1 + -5y)(3 + -2y) = 0Subproblem 1
Set the factor '(1 + -5y)' equal to zero and attempt to solve: Simplifying 1 + -5y = 0 Solving 1 + -5y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5y = 0 + -1 -5y = 0 + -1 Combine like terms: 0 + -1 = -1 -5y = -1 Divide each side by '-5'. y = 0.2 Simplifying y = 0.2Subproblem 2
Set the factor '(3 + -2y)' equal to zero and attempt to solve: Simplifying 3 + -2y = 0 Solving 3 + -2y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -2y = 0 + -3 -2y = 0 + -3 Combine like terms: 0 + -3 = -3 -2y = -3 Divide each side by '-2'. y = 1.5 Simplifying y = 1.5Solution
y = {0.2, 1.5}
| 8/7= | | x+56=90 | | 9/23= | | t=240 | | 3x-2Y=5XY | | 6.8c-5=25.4 | | x^2-6x+5=4 | | x/25=1 | | Y=-0.25+2x | | 51/.34 | | 2x+x+1=4x+1 | | x^2-9y^2=22 | | 12m+5-2m-13= | | 4x-50=110 | | x^-8/y^-7 | | Y=2x-0.25 | | 1/4y=32 | | 3c-3=12-3 | | 4(u-5)-1=-4(-4u+4)-2u | | h/9=15/10 | | 1/3k=18 | | 3x+145=180 | | 7/2=56/w | | 2/7=56/w | | 12xn=67 | | 1-3c=9 | | (8y+5)+(3y-1)+(4y+13)+(5y+3)=360 | | 3v+16=7v | | 35=-3x+8+5x | | onethirdc=9 | | 3x-5x-3x+2y-3x+5-y= | | 4x+15y=628 |